ASSESSING THE EFFECTIVENESS OF VISUAL CONTENT IN DIGITAL MARKETING CAMPAIGNSIN ITS IMPLEMENTATION IN THE TODAY'S COFFEE SHOP BUSINESS SECTOR - Muh. Husriadi; Citra Ayu Ningsi; Iwan Patta (Adisam Publisher, 2025)
The rapid development of the contemporary coffee shop sector demands an effective digital marketing strategy, especially in utilizing visual content to attract young and urban audiences. This study aims to evaluate the effectiveness of visual content in digital marketing campaigns in contemporary coffee shops and identify production challenges and adaptive solutions applied. The research method uses a qualitative approach with case studies and in-depth interviews and observations of coffee shop business actors who are active on social media. The results of the study show that quality product photos, videos of the coffee making process, and content of the shop atmosphere are the dominant types of visual content that can increase engagement, purchase interest, and customer loyalty. However, limited resources such as time, cost, and technical expertise are significant obstacles in the production of quality content that are overcome through independent training and the use of simple editing applications. These findings provide an important contribution to the digital marketing literature in the creative MSME sector and serve as a practical guide for business actors in optimizing visual content strategies to improve digital marketing performance.